ANALISIS KELAYAKAN DAN STRATEGI PENGEMBANGAN WILAYAH DALAM WACANA PEMBENTUKAN DAERAH OTONOM BARU BOGOR TIMUR - Aan Nurhasanah; Bambang Juanda; Eka Intan Kumala Putri (TATALOKA, 2018)
ABSTRACTBogor District as one of large region and large number of population has any problems related to accesibility and equity welfare.  Regional proliferation considered as a way to overcome that problems.  The study used scoring method based on PP no. 78 2007 with descriptive analysis, location quotient analysis, and Klassen Tiphology. This study was aimed to analyzed feasibility of regional proliferation and to formulate regional development strategy based on economic potentials in eastern Bogor District region. In general the result showed that eastern Bogor District region appropriate to organize as an autonomous region.  High economic potential and fiscal cappacity of eastern Bogor region can be made as main factor to recommended eastern Bogor District region as an autonomous region.  Thus, the selected strategies are how to develop backward regions base on leading sector, support primary sector development such as agricultural. Goverment policy is important to optimize natural resources management, spread out infrastructure development mainly to support rural area development. The implication of policy directed base on each region characters such as social, culture, spatial, basic sector.   Furthermore regional development analysis can be set base on sub-district region.